Design, development, and control of a tough electrohydraulic hexapod robot for subsea operations. (3rd May 2018) - Davliakos, I.; Roditis, I.; Lika, K.; Breki, Ch.-M.; Papadopoulos, E.
Abstract: In this paper, the design, the development, and the control for an 18 degree-of-freedom electrohydraulic hexapod robot for subsea operations are presented. The hexapod, called HexaTerra, can be equipped with a trenching machine, and move over obstacles and on sloped terrain. Optimization techniques are employed to size the robot legs. Rigid body equations of motion and hydraulic dynamics are developed. Compact electrohydraulic components are sized and selected taking into account the leg kinematics and system dynamic analysis. A model-based control system design is implemented in a real-time environment, able to produce the overall functionality and performance. Experimental results obtained from preliminary tests with the developed electrohydraulic hexapod show good controlled performance and demonstrate excellent system stability over obstacles. Abstract :